Comparative effectiveness of teriflunomide and dimethyl fumarate in patients with relapsing forms of MS in the retrospective real-world Teri-RADAR study. (13th February 2019) - Zivadinov, Robert; Kresa-Reahl, Kiren; Weinstock-Guttman, Bianca; Edwards, Keith; Burudpakdee, Chakkarin; Bergsland, Niels; Dwyer, Michael G; Khatri, Bhupendra; Thangavelu, Karthinathan; Chavin, Jeffrey; Mandel, Matt; Cohan, Stanley
Aim: Head-to-head clinical trials of teriflunomide (TFM) versus dimethyl fumarate (DMF) have not been conducted.Objectives: To compare the real-world effectiveness of TFM versus DMF.Methods: Anonymized data were collected from patients with relapsing multiple sclerosis (MS) initiating treatment with teriflunomide (N = 50) or DMF (N = 50).Results: On follow-up magnetic resonance imaging (MRI) compared with baseline, with TFM versus DMF treatment, the proportion of patients with new/enlarging T2 or gadolinium-enhancing lesions was 30.0 versus 40.0% (p = 0.2752). However, median annualized percent whole brain volume change was -0.1 versus -0.5 (p = 0.0212). There were no significant treatment differences on additional MRI and clinical end points and no unexpected safety signals.Conclusion: The effectiveness of teriflunomide was superior to DMF on whole brain atrophy and similar to DMF on other MRI/clinical end points.